Challenges of Islamic debt restructuring in a multi creditor environment - Abd Hafiz, Rozita; Abu Samah, Zariah; Hassan, Rusni (IIUM Press, 2017)
The growth of Islamic Finance over the last few decades has brought Islamic Finance to a level where it co-exists hand in hand with conventional banking. It is now common for the same customer to take up both Islamic financing and conventional loans as opposed to only conventional loans in the past. While such development is positive, there are inherent issues resulting from such co-existence. One notable issue is when default occurs due to non-payment by the customer, and when both the Islamic financier (Islamic creditor) and the conventional lender (conventional creditor) subsequently opt for debt restructuring instead of proceeding with insolvency action. Debt restructuring helps prevent further default, thus can assist in preserving the business value of the customer and the interests of the creditors as a whole. It is not a difficult task if a customer has one creditor only. However, the situation can become complex when the debt of both the Islamic and conventional creditor are to be restructured concurrently. This situation is referred to as Multi-Creditor debt restructuring. While the objective of a Multi-Creditor Debt Restructuring is beneficial to all creditors and the customer, there are challenges for Islamic debt restructuring in a Multi-Creditor situation such as differing creditor’ rights, multiple interpretation on Shari’ah contracts and lack of clarity in documentation of transactions. These could lead to difficulties, amongst others, in proving the right amount of debts due and owing as well as in ascertaining the priority of claims vis-a-vis conventional loans. This research discusses some of the key issues faced when restructuring Islamic debts in a Multi-Creditor situation and how those issues and gaps are to be addressed with some recommended process flow, procedures and guidelines.